The Effect of Oxytocin Massage on Increasing Milk Production - Kartini Kartini; Atnesia Ajeng; Fitri Suaningsih (Universitas Muhammadiyah Tangerang, 2020)
Introduction Based on the research of the World Health Organization (WHO) at 2012 in six developing countries, the risk of death from infants aged 9-12 months increased by 40% if not breastfed, whereas infants under 2 months of increase reached 48%. Exclusive breastfeeding can reduce child mortality by 13%. Breast milk production is influenced by the hormone prolactin, while expenditure is influenced by the hormone oxytocin. Massage oxytocin is one solution to overcome the lack of launch production of milk in the whole spine (vertebrae) bone costae to the fifth-sixth and an attempt to stimulate the hormones prolactin and oxytocin after labour.Research Methodology The research uses quasi-experiment and samples taken as many as 30 people postpartum mothers who gave birth in a health center Balaraja, 15 people used as the control group, and 15 people used as the intervention group. The sampling technique in this research used Accidental Sampling.The results of the research there was a significant effect of massage oxytocin to increase milk production P = 0.000, no significant effect of massage oxytocin to increase BB baby P = 0.000, no significant effect of massage oxytocin with frequency BAK baby P = 0.679, there was no significant effect of massage oxytocin-the frequency of bowel baby P = 0.075.The conclusion from this research is there a massage effect of oxytocin on lactation and infant BB and no massaging effect of oxytocin on the frequency of bladder and bowel baby. Her recommendation is expected this research can be useful to add insight and knowledge and can be used as additional information for researchers in the future regarding oxytocin massage and for further research are expected to increase the number of samples to be research